Something from the nightside - Green, Simon R., 1955- (Green, Simon R., 1955- Novels of the Nightside., 2003)
Detective Taylor uses his gift as a child of the Nightside to help people find lost things, but when Joanna Barrett asks for his help finding her runaway daughter, Taylor is forced to return to the nightmares of his past to bring the girl home.